Comparative Study of COVID-19 Prevention Behavior in Health and Non-Health Students - Arrum Firda Ayu Maqfiroch; Siti Masfiah; Arif Kurniawan (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2022)
ABSTRACT Background: Covid-19 has become a pandemic. Indonesia is the second highest prevalence number in Southeast Asia (as of mid-September 2020). Prevention behaviors become the key strategy to block the spread of the disease because there is no vaccine ready yet. Methods: This study aims to compare the prevention behavior of Covid-19 between health students and non-health students. This was an observational study with a cross-sectional approach. Data was collected using structured questionnaire electronically. It is involved 271 students from health and non-health students. Wilcoxon test used to compare means of results. Study was approved ethically by health sciences ethical committee, Jenderal Sudirman University. Results: There was no different behavior between health students and non-health student, however it was found that there was a different of the perception cost related to behavior prevention and perception on community leader support between two groups. Conclusions: There was a different in perception cost related to heavior prevention and perception on community leader support between health and non-health student. It is an alarm for the sustainability of behavior. Keywords: covid-19, Indonesia, prevention behavior, students